The defense of Thaddeus A. Ledbetter a novel - Gosselink, John. (Laura Ann); Rosenstock, Jason L. 1978- 1906-1998. (New York Amulet Books, 2010)
Twelve-year-old Thaddeus A. Ledbetter, who considers it a duty to share his knowledge and talent with others, refutes each of the charges which have sent him to "In-School Suspension" for the remainder of seventh grade.
Keywords: Conduct of life -- Fiction; Middle schools -- Fiction; Student suspension -- Fiction; Humorous stories